Combining ability for seed yield and yield components in sunflower (Helianthus annuus L.) - Mohamed, Mohamed; Elzein, Ibrahim; Ahmed, Mohamed; Ibrahim, Abu Elhassan (Gezira Journal of Agricultural Science, 2015)
This study was conducted using four cytoplasmic male sterile lines (cms) and ten restorers of sunflower ( Helianthus annuus L.) in a line x tester fashions in summer and winter season of 2007at Sennar Research Station Farm, Agricultural Research Corporation, Sudan. The objectives were to determine the general combining ability and specific combining ability effects among 14 parents and their 40 crosses for seed yield and other agronomic traits. The experiment was carried out under supplementary irrigation using a randomized complete block design (RCBD) with three replicates. The traits studied were days to 50% flowering, plant height (cm), head diameter(cm), number of seeds per head, percentage of empty seeds, 1000-seed weight (g), and seed yield (kg/ha). Analysis of variance of the combining abilities revealed highly significant differences for general combining ability (GCA) and specific combining ability (SCA). The highest contribution to the total variance was expressed by SCA for most important traits. The non-additive gene effects were found to be important for the inheritance of all traits except for plant height which was controlled by additive gene effect in the base material. The cms lines SA3 and SA4 and restorers SR41, SR45, SR10 and SR13 were better general combiners for most of the traits including seed yield across two seasons. The best combining hybrids for seed yield in the combined analysis were SA4 x SR1, SA3 x SR41, SA4 x SR45, SA3 x SR13 and SA3 x SR10. The greatest average contribution to the expression of most of the traits was found in the line x tester interaction, while the contribution of the female (A-line) and the male (R-line) were less significant. The simple correlation analysis revealed that seed yield was positively and significantly correlated with 1000-seed weight, head diameter and number of seeds per head and negatively correlated with percentage of empty seeds. Thus, the highly significant SCA effects in the superior crosses could be utilized in heterosis breeding to develop of high yielding local single-cross hybrids or produce synthetic composite varieties.   أجريت هذه  التجربة بتهجين أربعة خطوط ذات عقم سايتوبلازمى ذكرى مع عشرة خطوط معيدة لخصوبة من محصول زهرة الشمس باستخدام تحليل  Line x Testerفي موسمي صيف وشتاء 2007 بمحطة  بحوث سنار– السودان لتقدير المقدرة العامة والخاصة على التآلف لإنتاجية البذور ومكونتها لأربعة عشر من الآباء وأربعين من هجن الزهرة. أجريت التجربة بالقطاع المروى باستخدام تصميم القطاعات العشوائية الكاملة بثلاثة مكررات. كانت الصفات المدروسة هي عدد الأيام حتى 50% إزهار ، طول النبات، قطر القرص ، عدد البذور بالقرص، نسبة البذور الفارغة، وزن الآلف حبة، وإنتاج البذور (كيلوجرام/هكتار). أظهر تحليل التباين للقدرة على التالف قدرة الارتباط بين الآباء  وأهمية كل من الفعل الجيني الإضافي وغير الإضافي في توريث الصفات المدروسة. بيد أن تأثيرات الفعل الجيني الإضافي كانت مهمة في توريث صفة طول النبات وأن الفعل الجيني غير الإضافي كانت مهمة في توريث معظم الصفات المدروسة.  تأثيرات القدرة العامة للاتحاد أظهرت أن الأبوين العقيمين SA3 و SA4والآباء الخصبة SR13, SR10, SR45, SR41هم الأفضل في القدرة على الاتحاد العام لمعظم الصفات بما فيها صفة أنتاج البذور خلال الموسمين والتحليل المشترك. وأفضل قدرة للاتحاد الخاص لصفة أنتاج البذور في التحليل المشترك ، أظهرت بواسطة الهـــجن SA4 x SR1,  ، SA3 x SR41، SA4 x SR45 ، SA3 x SR 13  وSA3 x SR10.أظهرت الدراسة أن مساهمة تفاعل الآباء المذكرة مع الآباء المؤنثة في توريث معظم الصفات اكبر من مساهمة أي من الأبوين منفرداً. ارتبطت إنتاجية البذور ارتباطاً موجباً مع وزن الألف بذرة، وقطر القرص، وعدد البذور بالقرص وسلبياً مع نسبة البذور الفارغة. وعليه الفروقات المعنوية الكبيرة لتأثير القدرة الخاصة على التآلف في التهجينات المتفوقة يمكن الاستفادة منها في برنامج التربية لتطوير هجن مفردة محلية من الزهرة ذات إنتاجية عالية من البذور أو في تطوير أصناف تركيبيه.